Effect of different obturation techniques on sealer penetration into dentinal tubules after final irrigation with XP-Endo Finisher File = Efecto de diferentes técnicas de obturación en la penetración del sellador en los túbulos dentinarios después de la irrigación final con XP-Endo Finisher File - Demir, Erhan; Göker Kamalı, Selin; Türkaydın, Dilek (2023)
The first objective of this research was to evaluate the effectiveness of XP-Endo Finisher on dentinal tubule penetration of irrigation solution using confocal laser scanning microscopy. The main purpose of this research was to compare the effect of cold lateral condensation, continuous wave obturation and core-carrier based techniques on sealer penetration. Sixty mandibular premolars were prepared and allocated into two experimental groups (n=30) as the final irrigation technique and obturation technique experiment. In the final irrigation technique experiment, final irrigation was performed with XP-Endo Finisher, passive ultrasonic irrigation (PUI) and conventional needle irrigation (CNI) (n=10). The roots in the obturation technique experiment were also assigned into 3 groups and obturated with cold lateral condensation, continuous-wave obturation and core-carrier techniques (n=10). The most effective activation method, which emerged as a result of the first part of this study, was used as the final irrigation method in the obturation technique experiment. Then, all roots were sectioned in 1-mm-thick slices at 3mm from the apex for scanning. In terms of depth and percentage of material penetration, CNI exhibited significantly the lowest values and no significant difference was found between others. Also, there was no significant difference among obturation methods. In conclusion, XP-Endo Finisher and PUI are more effective than CNI on irrigant penetration. Sealer penetration into dentinal tubules is independent of obturation techniques.
El objetivo principal de esta investigación fue evaluar la eficacia de XP-Endo Finisher en la penetración de la solución de irrigación en los túbulos dentinarios mediante microscopía de láser confocal. Se prepararon sesenta premolares mandibulares y se distribuyeron en dos grupos experimentales (n=30) según el tipo de método de evaluación utilizado. En el experimento de la técnica de irrigación final, la irrigación final se realizó con XP-Endo Finisher, irrigación ultrasónica pasiva (PUI) e irrigación con aguja convencional (CNI) (n=10). Las raíces en el experimento de la técnica de obturación también se asignaron en 3 grupos y se obturaron con técnicas de condensación lateral fría, obturación de onda continua y portador de núcleo (n=10). El método de activación más eficaz, que surgió como resultado de la primera parte de este estudio, se utilizó como método de irrigación final en el experimento de la técnica de obturación. Luego, todas las raíces se seccionaron en muestras de 1mm de espesor. En términos de profundidad y porcentaje de penetración del material, CNI exhibió significativamente los valores más bajos y no se encontraron diferencias significativas entre los demás. Además, no hubo diferencias significativas entre los métodos de obturación. En conclusión, XP-Endo Finisher y PUI son más efectivos que CNI en la penetración del irrigante. La penetración del sellador en los túbulos dentinarios es independiente de las técnicas de obturación.
En revista Odóvtos, vol. 25, no.2 (mayo-agosto 2023)
Descripción basada en el contenido visto el 17 de diciembre, 2024
También disponible en formato HTML y EPUB